FORMULASI DAN UJI ANTIJAMUR Candida albicans KRIM EKSTRAK RIMPANG KENCUR (Kaempferiae galanga Linn.) DENGAN VARIASI ASAM STEARAT DAN TRIETANOLAMIN - Irawan, Ira; Aisiyah, Siti; Purwaningsih, Desi (Jurnal Farmasi (Journal of Pharmacy), 2023)
The active compounds contained in the rhizome of kencur (Kaempferia galanga Linn.) include alkaloids, flavonoids, and tannins which are used as antifungals. This study aims to determine the effect of variations of stearic acid and triethanolamine on the physical quality and stability of cream preparations and their activity against Candida albicans ATCC 10231 and cream formulation formulas with the best physical quality and have antifungal activity. Kencur rhizome extract was obtained by maceration using 70% ethanol and formulated with an extract concentration of 12% and variations of stearic acid and triethanolamine with a ratio of (10:7, 13:5, 16:3). The formulation of the cream preparation was carried out by mixing the oil phase and the water phase and then physical quality was carried out including organoleptic tests, homogeneity, spreadability, adhesion, pH, viscosity, and Cycling test. This study used the disc diffusion method to determine antifungal activity and one way ANOVA for statistical analysis. The results showed that the diameter of the extract inhibition zone was 13.17 mm. Variations of stearic acid and triethanolamine affect the physical quality and antifungal activity of cream preparations. Cream preparations have antifungal activity against Candida albicans ATCC 10231. The best formula is formula 1 with variations of stearic acid : triethanolamine (10:7) which has the best physical quality, with an inhibition zone diameter of 13.00 mm which is strong in inhibiting fungal growth.